The plus one - Lalli, S. C. (William Morrow & Co., 2024)
The wedding of Radhika Singh and Raj Joshi, a weeklong affair at a luxury resort in Cabos, isn't just going to be the event of the season, it will also mark the union of two highly influential and wealthy Indian-American families. No expense will be spared for what Radhika and Raj have coined "R&R," a week of rest, relaxation, and celebrating their love. Shaylee "Shay" Kapoor is just an outsider, but she just so happens to be dating Raj's best friend, Caleb Prescott III, and is sucked into this world of wealth and excess. But on the morning the wedding festivities are supposed to begin, the resort's wedding coordinator Daniela makes a frightening discovery: Raj and Radhika are dead, gunshots to the head. Chaos descends on the hotel as the guests are turned away or sent home. Shay stays by Caleb's side as the investigation starts to unfold, family and close friends grieve, and accusations run wild. The police believe the murders are a drug cartel hit. But even if it was a cartel hit, even if the murderer somehow got past the resort's security, the hotel room doors have state-of-the-art locks. There was no way for the murderer to slip into the room without a key. And only the sister of the bride, Zara; the best men, Caleb and Sean; and the wedding coordinator, Daniela, have keys. Shay may be an outsider, and she definitely has secrets of her own, but she may be the only person with enough perspective to untangle everyone's lies, and discover why anyone would want the bride and groom dead.